Enhanced Sampling in Molecular Dynamics Simulations: How Many MD Snapshots can be Needed to Reproduce the Biological Behavior? - Tavares, Camila A; Santos, Taináh M R; Gonçalves, Mateus A; da Cunha, Elaine F F; Ramalho, Teodorico C (Mini reviews in medicinal chemistry, 2024)
Since its early days in the 19th century, medicinal chemistry has concentrated its efforts on the treatment of diseases, using tools from areas such as chemistry, pharmacology, and molecular biology. The understanding of biological mechanisms and signaling pathways is crucial information for the development of potential agents for the treatment of diseases mainly because they are such complex processes. Given the limitations that the experimental approach presents, computational chemistry is a valuable alternative for the study of these systems and their behavior. Thus, classical molecular dynamics, based on Newton's laws, is considered a technique of great accuracy, when appropriated force fields are used, and provides satisfactory contributions to the scientific community. However, as many configurations are generated in a large MD simulation, methods such as Statistical Inefficiency and Optimal Wavelet Signal Compression Algorithm are great tools that can reduce the number of subsequent QM calculations. Accordingly, this review aims to briefly discuss the importance and relevance of medicinal chemistry allied to computational chemistry as well as to present a case study where, through a molecular dynamics simulation of AMPK protein (50 ns) and explicit solvent (TIP3P model), a minimum number of snapshots necessary to describe the oscillation profile of the protein behavior was proposed. For this purpose, the RMSD calculation, together with the sophisticated OWSCA method was used to propose the minimum number of snapshots.
Keywords: computational chemistry.; farmaceutická chemie; AMP-Activated Protein Kinases; Algorithms; Medicinal chemistry; conformational choice; Molecular Dynamics Simulation; Quantum Theory; kvantová teorie; simulace molekulární dynamiky; OWSCA; lidé; molecular dynamics; proteinkinasy aktivované AMP; snapshots; algoritmy; Humans; Chemistry, Pharmaceutical